Common adverse events following immunization with the COVID-19 comirnaty vaccine (Pfizer-BioNTech) among adult population in Hanoi, Vietnam, 2021 - Le, Xuan Thi Thanh; Hoang, Quan Long; Ta, Nhung Thi Kim; Pham, Quan Thi; Nguyen, Thao Thanh; Phan, Huong Thi Mai; Nguyen, Thanh Van; Le, Ha Thi Thanh; Nguyen, Nam Thuy; Hoang, Linh Dieu; Luong, Phuong Thi Huyen; An, Lien Hong; et al. (Frontiers in Tropical Diseases, 2022)
Rationale To prevent and control the COVID-19 pandemic, the biggest immunization campaign in history had been deployed worldwide. Therefore, it is important to inform the adverse events following immunization (AEFI) to populations. Objectives To prevent vaccine hesitancy, this study focused on finding the common AEFI with the COVID-19 Comirnaty vaccine (Pfizer-BioNTech) among participants aged 18 and above and related factors in Hanoi, Vietnam. Methods A cross-sectional study was carried out to collect participants’ data and AEFI after being vaccinated at Hanoi Medical University, Vietnam, in 2021. Logistic regression was utilized for analyzing the correlated factors of AEFI. Results We recruited a random sample of 820 participants who received both basic doses of Pfizer vaccine in September and October 2021. The proportion of AEFI after the first dose, second dose, and both doses of Pfizer vaccine was 24.4%, 64.2%, and 18.5%, respectively. AEFI mostly appeared within 1 day and lasted for 1 to 2 days. The AEFI were more common in females (OR=1.7; 95%CI=1.25–2.29) and younger age groups (OR=1.9; 95%CI=1.37–2.58). History of allergy, allergic diseases, chronic diseases, and occupations were not statistically significant with AEFI. Conclusion Our findings indicated that the COVID-19 Comirnaty vaccine is safe to be injected. Gender and age group are important factors influencing AEFI.